Laser printed microelectronics - Yang, Liang; Hu, Hongrong; Scholz, Alexander; Feist, Florian; Cadilha Marques, Gabriel; Kraus, Steven; Bojanowski, Niklas Maximilian; Blasco, Eva; Barner-Kowollik, Christopher; Aghassi-Hagmann, Jasmin; Wegener, Martin (Nature Communications, 2023)
Printed organic and inorganic electronics continue to be of large interest for sensors, bioelectronics, and security applications. Many printing techniques have been investigated, albeit often with typical minimum feature sizes in the tens of micrometer range and requiring post-processing procedures at elevated temperatures to enhance the performance of functional materials. Herein, we introduce laser printing with three different inks, for the semiconductor ZnO and the metals Pt and Ag, as a facile process for fabricating printed functional electronic devices with minimum feature sizes below 1 µm. The ZnO printing is based on laser-induced hydrothermal synthesis. Importantly, no sintering of any sort needs to be performed after laser printing for any of the three materials. To demonstrate the versatility of our approach, we show functional diodes, memristors, and a physically unclonable function based on a 6 × 6 memristor crossbar architecture. In addition, we realize functional transistors by combining laser printing and inkjet printing.
Gesehen am 23.08.2023